2014
DOI: 10.1155/2014/672123
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Effects of Soil Conditions on Olive Productivity in Mediterranean Hilly Areas

Abstract: The majority of olive (Olea europaea L.) production in Mediterranean environments is characterized by low external inputs and is practiced in hilly areas with shallow soils. This study aimed to study the yield and nutritional status for olive (cv. "Zeiti") trees in northwestern Syria and establish correlations between yield, on the one hand, and soil/land factors and tree nutrition, on the other hand, to determine the most yield-affecting factors. Land and soil fertility parameters (field slope, soil depth, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…A study carried out in Syria revealed that the olive yield variability was explained at 68% by the amount of potassium available in the root zone, followed by total N with 58% and mineral N with 44% [5]. The same study showed the absence of correlation between yield and leaf N and P contents and a significant correlation (26%) between yield and leaf K content.…”
Section: Correlation Between Parameters Studiedmentioning
confidence: 94%
“…A study carried out in Syria revealed that the olive yield variability was explained at 68% by the amount of potassium available in the root zone, followed by total N with 58% and mineral N with 44% [5]. The same study showed the absence of correlation between yield and leaf N and P contents and a significant correlation (26%) between yield and leaf K content.…”
Section: Correlation Between Parameters Studiedmentioning
confidence: 94%
“…This common practice contributes to increases in both biodiversity and soil conservation, preventing worrying rates of soil erosion. Indirectly, both natural and cultural heritage could be potentiated through agro-ecotourism [2,21,32,33].…”
Section: Characterization Of the Traditional Olive Orchard In Northea...mentioning
confidence: 99%
“…Unlike many fruit tree crops, olive trees can be well established on calcareous soils; however, they can also thrive in moderately acidic soils, with pH levels varying between 5.5 and 8.5. However, olive trees benefit from near-neutrality values due to the increase in nutrient absorption capacity as a consequence of the higher soil microbial activity (i.e., accelerates the mineralization process) [4,32,50]. In terms of physical properties, the soil texture and depth are limiting factors of the olive tree's productive cycle, since they influence the soil water holding capacity, an effect that can be minimized through the implementation of cover crops and/or by adding organic matter.…”
Section: Soilsmentioning
confidence: 99%
“…In this study, the average olive yields for all experimental plots in 2015, 2016, 2017, and 2018 were 17.3, 5.5, 15.0, and 18.7 kg tree −1 , respectively. In this context, according to Tubeileh et al (2014), for rainfed plantations, the olive yield varied considerably from 6.0 to 65.0 kg tree −1 .…”
Section: Olive Yieldmentioning
confidence: 99%